Sulfur Biogeochemical Cycling and Redox Dynamics in a Shale‐Dominated Mountainous Watershed. Issue 6 (13th June 2022) - Fox, Patricia M.; Carrero, Sergio; Anderson, Cam; Dewey, Christian; Keiluweit, Marco; Conrad, Mark; Naughton, Hannah R.; Fendorf, Scott; Carroll, Rosemary; Dafflon, Baptiste; Malenda‐Lawrence, Helen; Dwivedi, Dipankar; et al.
Abstract: Sulfur (S) is an essential macronutrient and important component of the earth's crust, and its cycling has critical impacts on trace metal mobility, water quality, and human health. Pyrite weathering is the primary pathway by which sulfur enters surface waters. However, biogeochemical cycling of sulfur in soils and the river corridor mediates sulfate exports. In this study, we identified the major forms of sulfur across multiple compartments and scales in a pristine mountainous watershed, including shale bedrock weathering profiles, hillslope soils, and alluvial floodplain sediments, in order to provide insight into biogeochemical sulfur cycling in a hydrologically variable alpine system. X‐ray absorption near‐edge spectroscopy (XANES) analysis of shale weathering profiles showed clear evidence of pyrite oxidation to sulfate, with large accumulations of intermediate S(0) (20%–53%). Micro‐scale XANES showed evidence of reprecipitation of pyrite at fracture surfaces within the permanently saturated zone. Organic sulfur dominated S speciation in shallow hillslope soil and floodplain sediment, with little evidence of reduced inorganic S. However, mackinawite formation, representing active sulfate reduction, was observed in saturated oxbow sediments and saturated weathered shale underlying floodplain sediments. Further evidence of sulfate reduction from aqueous sulfur isotopic analysis was observed in shallow groundwater transects across an Fe‐reducing meander, whereas increases in pore water sulfate concentrations implied sulfur oxidation at other locations. The data present an integrated picture of sulfur cycling in a shale‐dominated watershed, where riverine sulfate exports are mediated by biological cycling, particularly in redox‐stratified and temporally dynamic hyporheic zone sediments. Plain Language Summary: Sulfur is an essential macronutrient and biologically important component of the earth's crust, and its cycling has critical impacts on water quality and human health. Weathering of the mineral pyrite from rock is the primary pathway by which sulfur enters surface waters, and alterations to the hydrologic cycle due to climate change may affect pyrite weathering rates. However, biological cycling of sulfur in soils and the river corridor mediates the release of sulfur to rivers and the ocean. In this study, we identified the major forms of sulfur across a pristine mountainous watershed, including shale bedrock weathering profiles, hillslope soils, and alluvial floodplain sediments. Shale weathering profiles showed pyrite conversion to sulfate, with large accumulations of intermediate elemental sulfur. In the river corridor, precipitation of the mineral mackinawite was observed in water‐saturated sediments. By contrast, organic sulfur compounds were the primary forms of sulfur in shallow, unsaturated hillslope soil and floodplain sediment, demonstrating the importance of biological sulfur cycling in these zones. The data present an integrated picture of sulfur cycling in a shale‐dominated watershed, where riverine sulfate exports are controlled by a balance of rock weathering and biological cycling, particularly in the hydrologically and biologically dynamic river corridor. Key Points: Bedrock shale weathering profiles show pyrite oxidation to elemental Sulfur (S) and sulfate, with reprecipitation of pyrite at fracture surfaces Organic‐S compounds dominate S speciation in unsaturated hillslope soil and floodplain sediment River corridor processes, such as biological uptake and reduction may attenuate sulfate releases from oxidative pyrite weathering